2017
DOI: 10.3389/fpsyg.2017.00101
|View full text |Cite
|
Sign up to set email alerts
|

Time Perspective and Age: A Review of Age Associated Differences

Abstract: We investigate the relationship between age and the five dimensions of time perspective measured by the Zimbardo Time Perspective Inventory (ZTPI) (past negative, past positive, present hedonistic, present fatalistic, and future). Time perspective is related to well-being, decision-making, level of development, and many other psychological issues. Hence, the existence of a systematic relationship between time perspective and age should be considered in all studies for which time is a relevant variable. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
12

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 73 publications
3
38
0
12
Order By: Relevance
“…Other scholars observe that individuals give more attention to the present as they grow older (Zhang & Ho, 2015). Still other research results support the hypothesis suggesting that people in general focus more on the past (Laureiro-Martinez, Trujillo, & Unda, 2017). Similar discrepancies are found in studies on gratitude and age associations.…”
Section: Gratitude Time and Agesupporting
confidence: 78%
See 1 more Smart Citation
“…Other scholars observe that individuals give more attention to the present as they grow older (Zhang & Ho, 2015). Still other research results support the hypothesis suggesting that people in general focus more on the past (Laureiro-Martinez, Trujillo, & Unda, 2017). Similar discrepancies are found in studies on gratitude and age associations.…”
Section: Gratitude Time and Agesupporting
confidence: 78%
“…Although research on time perspective and gratitude seems clear, a review of the studies on the association between time perspectives and age (Mello & Worrel, 2015) as well as between trait gratitude and age (Chopik, Newton, Ryan, Kashdan, & Jarden, 2017;Froh, Kashdan, Ozimkowski, & Miller, 2009) is not free of inconsistencies and inconclusive findings (Laureiro-Martinez, Trujillo, & Unda, 2017). Some researchers suggest that young people focus more on the future and less on the past and the present (Mello & Worrel, 2006).…”
Section: Gratitude Time and Agementioning
confidence: 99%
“…Similarly, younger participants were more likely to focus on the present than their older counterparts, in study of individuals aged 8-90 years old who were from America, Europe, and Puerto Rica (Gonzalez & Zimbardo, 1985). Regarding time feelings, a meta-analysis of studies with individuals aged 13 to 75 indicated that negative attitudes toward the past were inversely associated with age (Laureiro-Martinez, Trujillo, & Unda, 2017).…”
Section: Time Perspective Is Developmentalmentioning
confidence: 99%
“…In addition to a heavy reliance on undergraduate samples, Zimbardo and Boyd (1999) admitted that their focus on individualistic cultures also limited their validation efforts. In response, the ZTPI has been administered across the globe (Cretu & Negovan-Zbaganu, 2013;Laureiro-Martinez, Trujillo, & Unda, 2017).…”
Section: The Zimbardo Time Perspective Inventorymentioning
confidence: 99%